TINJAUAN KETIDAKLENGKAPAN PENGISIAN ASESMEN AWAL MEDIS RAWAT INAP PASIEN BEDAH GUNA MENUNJANG KUALITAS INFORMASI REKAM MEDIS DI RSUD AL IHSAN PROVINSI JAWA BARAT - Monica, Rizqy Dimas; Pujilestari, Intan; Nopiyanti, Sabila (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDC, 2023)
The importance of the completeness of filling in the Initial Medical Assessment is one indicator of the quality of information in the medical record file, which according to Kepmenkes 129 / Menkes / SK / II / 2008 states that the completeness of filling in medical record files must be filled in 24 hours after completion of medical services in the hospital is 100%. Based on the results of preliminary studies conducted, the authors took a sample of medical record files of surgical patients in February as many as 30 files, out of 30 files there were 20 files (66.66%) of the patient's initial medical assessment form that had not been completely filled in. The purpose of this study was to determine the completeness of filling out the initial medical assessment of surgical patient hospitalization. The research method used is descriptive method with quantitative approach. The population in this study was the initial medical assessment form for inpatient surgical patients in November-January 2023 at Al Ihsan Hospital, West Java Province, totaling 209 files. The sample taken from the population was 68 samples. The data collection techniques used were observation, interview, and documentation. The results of the research conducted by the author, showed that of the 68 samples of initial medical assessment sheets in November-January 2023, namely for the completeness of filling out the initial medical assessment in the patient identification variable of 50 files (74%). The variable of filling in reports / important notes amounted to 35 files (51%). Author authentication variable of 55 files (81%). The variable of good and correct recording was 67 files (98%) and the average completeness of filling out the initial medical assessment form for inpatient surgical patients in November-January 2023 was 76%.